The Lego ideas book : you can build anything - Lipkowitz, Daniel (London : DK, 2011)
Six themed chapters offer inspiration for LEGO creations, with basic templates and instructions for creating new things out of LEGO bricks and sets.
6.6
3-6.
3-6
Keywords: LEGO toys -- Juvenile literature; Models and modelmaking -- Juvenile literature; LEGO toys; Models and modelmaking; LEGO toys; Models and modelmaking